The Effects of Property Price Volatility, Rent Flows and Foreclosure Costs on Rational Discrimination in Mortgage Lending - Nickerson, David (Modern Perspectives in Economics, Business and Management Vol. 6, 2021)
Observations of significant differences in access to credit, loan terms and the volume of lending between demographically distinct groups of borrowers are often interpreted as evidence of potential ethnic, racial or gender discrimination by lenders. The competitive structure of credit markets and the accuracy of measuring individual credit risk render extant models of lending discrimination based on assumptions of credit market inefficiencies, such as adverse selection, increasingly implausible. In stark contrast to existing models of demographic discrimination, we consider a model of mortgage lending in an economy having complete markets, common knowledge and arbitrage-free pricing. Market equilibria in this classical environment may exhibit discrimination even when borrowers, who are distinguished only by observable demographic traits, share an identical measure of individual credit risk. Relatively costlier loan terms, a higher frequency of loan denials, or a complete rationing of credit to a particular demographic class of borrowers may be a value-maximizing strategy when rational lenders perceive that one or more such traits are directly related to adverse features of the representative property securing the loan to a borrower in this class. Omitted from standard statistical underwriting and regulatory review procedures, these features reduce the value of the collateral available to the lender in the event of future default. When loans are secured by such properties and both lenders and borrowers act strategically, discrimination on this basis will be a property of all market equilibria and can be consistent with an efficient allocation of credit.